Analisis Rekam Medis untuk Menentukan Pola Kelompok Penyakit Menggunakan Algoritma C4.5 - Rian Rafiska; Sarjon Defit; Gunadi Widi Nurcahyo (Jurnal RESTI (Rekayasa Sistem dan Teknologi Informasi), 2018)
The Medical Record contains records and documents of patient identity, examination results, treatment, actions and services provided to the patient. Medical records are very important for patient care because with complete data can provide information in determining diagnostic and clinical decisions. The completeness of the medical record determines the quality of the services provided. Regarding the pattern of the tendency of disease suffered by a group of people still not excavated to be used as a reference when doing panyuluhan or prevention of disease. Finding a common pattern of disease groups in the community based on the International Classification of Diseases (ICD) -X. In this study used the classification method with algorithm C4.5 with the amount of data as much as 709 sourced from the Medical Record of General Hospital General Hospital (RSUD) Major General H.A Thalib Kerinci. Determination of the next analysis is to apply the grouping into several attributes, namely group of regions, age groups, disease groups and groups of sex. Further data is processed and done by using Rapid Miner software. The results of the calculation is a pattern that can be used to analyze patterns of disease tendency experienced by the community.